2023
DOI: 10.1111/1365-2745.14049
|View full text |Cite
|
Sign up to set email alerts
|

Common and lifestyle‐specific traits of mycorrhizal root metabolome reflect ecological strategies of plant–mycorrhizal interactions

Abstract: 1. Mycorrhizas are widespread below-ground symbioses formed between plant roots and soil fungi. This plant-fungal partnership impacts terrestrial ecosystems by mediating plant performance and biogeochemical processes. The influence of mycorrhizas on plant and ecosystem functioning is ultimately driven by the biological processes that regulate plant-mycorrhizal interactions. Although convergent patterns in morphological and genetic traits of mycorrhizas have been well-documented and reflect key selection forces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…Previous studies focusing on metabolic changes in response to ectomycorrhizal symbiosis mainly compared the differences between EM and non‐EM roots (Szuba et al, 2020; Sebastiana et al, 2021; Xia et al, 2023). Compared with non‐inoculated roots, mycorrhization mainly changes primary metabolites including amino acids, organic acids and carbohydrates (Xia et al, 2023), which were also regulated during symbiosis establishment in our dataset (Figure 3). Additionally, metabolism of long‐chain fatty acids and vitamin B6 were altered in roots of Quercus suber colonized by Pisolithus tinctorius (Sebastiana et al, 2021), which is similar to our results (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focusing on metabolic changes in response to ectomycorrhizal symbiosis mainly compared the differences between EM and non‐EM roots (Szuba et al, 2020; Sebastiana et al, 2021; Xia et al, 2023). Compared with non‐inoculated roots, mycorrhization mainly changes primary metabolites including amino acids, organic acids and carbohydrates (Xia et al, 2023), which were also regulated during symbiosis establishment in our dataset (Figure 3). Additionally, metabolism of long‐chain fatty acids and vitamin B6 were altered in roots of Quercus suber colonized by Pisolithus tinctorius (Sebastiana et al, 2021), which is similar to our results (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of CT also remained equivalent or decreased in response to AM and EcM colonization. Notably, a related study on the same sample sets as this study found that mycorrhizal colonization caused an accumulation of catechins, which are precursors to CT, in the roots of many plant–fungus combinations (Xia et al ., 2023). Taken together, these studies indicate that compounds produced in the phenylpropanoid pathway, even those that are biosynthetically related, can respond very differently to mycorrhizal colonization, potentially serving distinct functions.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary metabolites, such as avonoids belonging to phenylpropanoids, play a crucial role in maintaining the structural and functional integrity of cells, thereby mitigating oxidative damage caused by ROS. This protective mechanism aids plants in coping with drought stress [20,21]. AMF has been observed to signi cantly enhance anthocyanin and total avonoid concentrations in Medicago truncatula leaves [22].…”
Section: Discussionmentioning
confidence: 99%
“…Xia et al [21] demonstrated that mycorrhizae lead to the accumulation of root metabolites. However, the exact roles of these secondary metabolites induced by AM symbiosis in enhancing plant drought tolerance remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%